Building School Image Through Strategic Public Relations: A Multi-Strategy Framework in Indonesian Elementary Education - Irawati, Rohimah Aprilia; Roesminingsih, Erny; Karwanto, Karwanto; Khamidi, Amrozi (Papanda Publisher, 2025)
Public relations has evolved into a strategic imperative for educational institutions in managing reputation and stakeholder trust. However, research on public relations strategies in elementary schools, particularly in resource-constrained contexts, remains limited. This qualitative descriptive study examined public relations strategies at UPT SD Negeri 229 Gresik, Indonesia. Data were collected through semi-structured interviews with school principals, public relations coordinators, teachers, and parent representatives, complemented by participant observation and documentary analysis. The Miles and Huberman interactive model guided data analysis, with trustworthiness ensured through triangulation and member checking. Findings revealed five interconnected strategies: operational strategy emphasizing community-based familial approaches; persuasive-educational strategy employing multi-channel digital platforms achieving 78% Instagram engagement; social responsibility strategy demonstrating tangible community impact through 200+ trees planted and 150+ families assisted; collaborative strategy ensuring meaningful stakeholder participation; and coordinative-interactive strategy positioning the school within broader educational networks. These strategies collectively build positive school image by integrating cultural responsiveness with contemporary digital communication, extending public relations theory to elementary education contexts while providing actionable models for administrators navigating transparency and accountability demands in increasingly connected environments.